222k views
16 votes
-6x -6y = 66
2x + 4y = -32​

User Paba
by
5.2k points

1 Answer

9 votes

Answer:

(23/2, 1/2)

Explanation:

Let's solve this system through elimination by addition/subtraction:

Divide all three terms of the first equation by 3. This results in the equivalent system

-2x - 2y = 33

2x + 4y = -32

Combining like terms results in:

2y = 1, and so y = 1/2.

Let's use the first equation and y = 1/2 to find x:

-6x - 6(1/2) = 66

This becomes -6x - 3 = 66, or -6x = 69, or x = -69/6 , or x = 23/2

The solution is thus (23/2, 1/2)

-

User Lynnmarie
by
5.6k points